PENGARUH PEMBERIAN NAUNGAN DAN MULSA TERHADAP KADAR AIR TANAH DALAM PRODUKSI TANAMAN BAWANG MERAH PADA MUSIM PENGHUJAN - Rohman Wakhid; Suhardjo Widodo; Muharjo Pudjojono (Faculty of Agricultural Technology, University of Jember, 2012)
Onion (Allium ascalonicum L.) has a high demand and need, but it has not beenfollowed by an increase in production. This is due to the limitations of cultivation and to avoid the rainy season. Therefore, the need for shade and mulch to the planting medium that aims to control soil moisture and increase the production of onion plants effectively and efficiently. The study was conducted 7 shade and mulch treatments with 3 replications. Production control treatment weighing 70 grams and the amount of 18.7 tubers with soil moisture content (SMC) 35.8%; black-silver plastic mulch treatments weight of 426.7 grams the amount of 122.7 tubers SMC 34.4%; transparent plastic mulch treatments weight of 556.7 rams the amount of 174 tubers SMC 33.4%; silver plastic mulch treatments weight of 443.3 grams the amount of 130.7 tubers SMC 33.8%; paranet shade treatment weight of 80.7 grams the amount of 22.7 tubers SMC 35, 4%; straw mulch treatments weight of 46.7 grams theamount of 12.7 tubers SMC 36.5%; and vegetative shade treatment weight of 173.7 grams the amount of 51.3 tubers SMC 34.8%. Onion production in the rainy season can be done with plastic mulching.Keywords: providing shade and mulch, soil moisture content, production